Cigarette smoking patterns in relation to religiosity and familial support among Iranian university students: A Latent Class Analysis - Sima Afrashteh (Tobacco Induced Diseases, 2018)
Introduction Entering University is an important developmental milestone that might be associated with cigarette smoking. The aim of this study was to identify the subgroups of university students on the basis of cigarette smoking patterns, and to assess the role of familial support and religious beliefs on membership in specific subgroups.